Kadar Timbal (Pb) dalam Darah Sukarelawan Pengatur Lalu Lintas (Supeltas) di Kota Surakarta Ditinjau dari Usia, Lama Kerja dan Kebiasaan Merokok - Prabandari, Anggraeni Sih; Sari, Ajeng Novita; Pramonodjati, Fredericus; Wulandari, Tata (Indonesian Journal on Medical Science, 2024)
Lead (Pb) can enter the blood through inhalation. Traffic management volunteers (supeltas) has high risk of Pb exposure because they are often exposed to vehicle smoke containing Pb. In addition to occupational risks, high blood Pb levels can be affected by age, duration of exposure and smoking habits. This study aims to determine the level of lead in the blood of supeltas based on age, working period and smoking habits. It was descriptive analytical research with a cross sectional design. Sixteen men were involved in this research. Blood was drawn from their vein and added with EDTA anticoagulant. Pb levels in the blood were analyzed by the Flame Atomic Absorption Spectrophotometer (FAAS). The Spearman test was used to determine the strength of correlation of age, length of work and smoking habits on Pb levels. The average Pb level in the blood of the supeltas was 117.45 ?g/dL. The lowest level of Pb was found in the P10 and P5 samples, which was 3,7 ?g/dL, while the highest level in P16 was 668,7 ?g/dL. About 75% (12/16) of supeltas had high Pb blood levels. The results of Spearman's analysis showed that there was no significant relationship between blood lead levels and age (p-value 0,507>0,05), working age (p-value 0.976>0,05) and smoking habits (p-value 0,543>0,05).